Developing the case for enhanced landfill mining in the UK - Wagland, Stuart T.; Coulon, Frederic; Canopoli, Luisa (CISA Publisher, 2019)
Across the UK there are around 22,000 landfills sites, suggesting a significant opportunity for recovering value from previously discarded materials. Enhanced landfill mining (ELFM) has been identified as a concept to recover value from landfills through optimized valorization of the resources extracted. This approach, including waste-to-energy (WtE), waste-to-material (WtM) and waste-to-land (WtL) options can also assist in addressing critical and secondary raw material demands and scarcity. However, to date, there is still limited evidence on this potential. In this paper, the results of 9 UK landfill sites characterization and feasibility studies for ELFM are presented. Waste characterisation from 9 landfill sites located in the UK was carried out. Overall 36 core drills and 118 unique waste samples were analysed. High volumes of fines (soil-like) organic material were observed across all samples and significant levels of valuable metals were observed in this fraction. Previous work had determined significant aluminium and copper are contained in the soil-like fines fraction, which does not include the separate metals fraction (i.e. aluminium cans, copper wires etc). At one site the combustible fraction was assessed as a potential refuse-derived fuel [RDF]. Typically, 10-40% by weight of the samples at this site were ‘combustible’, with an average gross calorific value of 12.9 MJ/kg. Plastics extracted from the sites are contaminated and degraded, therefore further work is required to understand the extent of degradation and to assess available options upcycle these materials.
Keywords: Enhanced landfill mining; Waste composition; Landfill chemistry; Resource recovery; Secondary raw materials